'A Very Remarkable Ministry': John Charles Carlile C.H., C.B.E., D.D., D.Litt. (1861-1941). (3rd July 2022) - Shepherd, Peter
ABSTRACT: J. C. Carlile (1861-1941) was an English Baptist Minister, author and journalist. While at Spurgeon's Pastor's College he commenced his ministry in London dockland and actively participated in the 1889 London dockstrike. He was elected a member of the London School Board for the Borough of Southwark. Awarded a CBE for his wartime service during a 40 year ministry in Folkestone, in 1921 he was elected President of the Baptist Union of Great Britain. Later he briefly served as its General Secretary, and was for many years editor of the Baptist Times. In 1929 he was made a Companion of Honour. He made several visits to Canada and the USA, receiving honorary doctorates from two Canadian Universities. He was the author of several books, including The Story of the English Baptists (1905) and My Life's Little Day (1935).